Conformational properties, membrane interaction, and antibacterial activity of the peptaibiotic chalciporin A: Multitechnique spectroscopic and biophysical investigations on the natural compound and labeled analogs. Issue 5 (16th February 2018) - Biondi, Barbara; Peggion, Cristina; De Zotti, Marta; Pignaffo, Chiara; Dalzini, Annalisa; Bortolus, Marco; Oancea, Simona; Hilma, Geta; Bortolotti, Annalisa; Stella, Lorenzo; Pedersen, Jens Z.; Syryamina, Victoria N.; et al.
Abstract: In this work, an extensive set of spectroscopic and biophysical techniques (including FT‐IR absorption, CD, 2D‐NMR, fluorescence, and CW/PELDOR EPR) was used to study the conformational preferences, membrane interaction, and bioactivity properties of the naturally occurring synthetic 14‐mer peptaibiotic chalciporin A, characterized by a relatively low (≈20%), uncommon proportion of the strongly helicogenic Aib residue. In addition to the unlabeled peptide, we gained in‐depth information from the study of two labeled analogs, characterized by one or two residues of the helicogenic, nitroxyl radical‐containing TOAC. All three compounds were prepared using the SPPS methodology, which was carefully modified in the course of the syntheses of TOAC‐labeled analogs in view of the poorly reactive α‐amino function of this very bulky residue and the specific requirements of its free‐radical side chain. Despite its potentially high flexibility, our results point to a predominant, partly amphiphilic, α‐helical conformation for this peptaibiotic. Therefore, not surprisingly, we found an effective membrane affinity and a remarkable penetration propensity. However, chalciporin A exhibits a selectivity in its antibacterial activity not in agreement with that typical of the other members of this peptide class. Abstract :